PENGARUH SUPERVISI AKADEMIK TERHADAP KOMPETENSI DAN KINERJA GURU, DENGAN KOMITMEN GURU SEBAGAI MEDIASI - Astuti, Rini Juni; Nufus, Nur Aenun (Bussman Journal : Indonesian Journal of Business and Management, 2026)
This study aims to examine the extent of influence of Academic Supervision on Teacher Competence and Performance with Teacher Commitment as Mediator. The method used in this study uses saturated sampling. The number of samples used is 125 teachers. The quantitative data analysis technique in this study uses SEM-PLS (Structural Equation Modeling Partial Least Square) with SmartPLS 4 software. The results of this study indicate that Academic Supervision has a positive and significant effect on Teacher Competence. Academic Supervision has a positive and significant effect on Teacher Performance. Academic Supervision has a positive and significant effect on Teacher Commitment. Teacher Commitment has a positive and significant effect on Teacher Competence. Teacher Commitment has a positive and significant effect on Teacher Performance. Work motivation has a positive and significant effect on employee performance. Teacher Commitment mediates positively and significantly the effect of Academic Supervision on Teacher Competence. Teacher Commitment mediates positively and significantly the effect of Academic Supervision on Teacher Performance. The results of this study will contribute theoretically to the understanding and knowledge of Academic Supervision, Teacher Competence, Teacher Performance, and Teacher Commitment. This research is expected to provide lessons for elementary schools in Lape District regarding the importance of Academic Supervision in improving teacher competence, performance, and commitment. This study only involved elementary school teachers, so it cannot be generalized to other levels, such as junior high school (SMP) and senior high school (SMA) teachers.